Uncertainty and group identification: Moderation by warmth and competence as cues to inclusion and identity validation. Issue 5 (2nd September 2016) - Wagoner, Joseph A.; Hogg, Michael A.
Abstract: Drawing upon uncertainty-identity theory, we argue that self-uncertainty creates a motivated mindset in which people desire to have their social identity validated thorough inclusion, and that this transforms the meaning of group warmth and competence to cue inclusion. US College students ( N = 289) participated in an on-line experiment in which self-uncertainty and the perceived warmth and competence of their college were primed, and group identification was measured as the dependent variable. As predicted, the three-way interaction significantly affected group identification. Specifically, uncertainty weakened identification with cold-but-competent groups. We also found that uncertainty strengthened identification with cold-and-incompetent groups. This research highlights the preference for certain group attributes under uncertainty.